(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Indian microfinance is dominated by two operational approaches.The first approach is popularly known as SHG-Bank linkage model. This model is the dominant model, initiated by the NABARD through the SHG-Bank linkage programme in the early 1990s. Today the SHG model also links the informal groups of women to the mainstream system and it has the largest outreach to micro financial clients in the world.